Diversity and role of insects on vegetation around sugar palm (Arenga pinnata) plants in Tanjung Miring Village, Muara Enim Regency - Dhiva Kinanti Diadara; Weri Herlin (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Arenga pinnata (sugar palm) was a crop of high ecological, economic, and social in South Sumatra, particularly in Muara Enim Regency. Despite its importance, limited scientific information regarding the diversity and ecological functions of insect communities associated with this species. This study aimed to identify and classify insect taxa specifically decomposers, phytophagous, pollinators, and natural enemies found in and around sugar palm stands in Tanjung Miring Village. Field observations were conducted using purposive sampling, and insect specimens were collected through four established methods: yellow sticky traps, pitfall traps, sweep nets, and manual hand collection. A total of 850 insect individuals were recorded, with the greatest abundance observed on trees possessing trunk diameters between 31‒40 cm. Hymenoptera was the most frequently encountered order, with Monomorium minimum identified as the most dominant species. Among the collection methods, yellow sticky traps yielded the highest number of individuals. Biodiversity analysis revealed a Shannon-Wiener index (H′) of 2.47, indicating moderate diversity. The evenness index (E) was 0.73, suggesting relatively low species distribution uniformity, while the dominance index (D) was 0.13, implying the absence of a single dominant species within the community. Statistical analysis using NCSS software demonstrated a significant effect of trap type on insect abundance, but no significant differences were found based on insect order, tree diameter, or observation period. These findings underscore the ecological importance of insect diversity in sugar palm ecosystems, as various functional groups such as pollinators, herbivores, and decomposers play vital roles in supporting the growth, productivity, and sustainability.